Identifying How the Brazilian Software Industry Specifies Legal Requirements - Netto, Dorgival; Silva, Carla; Araújo, João (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
[Background] Software requirements are usually specified in Natural Language, bringing challenges for Requirements Engineering (RE) as these specifications are inherently ambiguous. These challenges become bigger when dealing with software requirements that must comply with regulations, the so-called legal requirements. The state of practice to tackle ambiguity of legal requirements and their compliance with regulations is missing. [Goal] This work investigates how ambiguity in legal requirements specification is addressed and how the software development industry performs legal compliance. [Method] We followed a qualitative approach based on semi-structured interviews involving nine professionals from different companies who presented their views on the RE process, including legal compliance and ambiguity resolution of legal requirements. Data was collected using audio-recorded and analyzed using Grounded Theory. [Results] Findings revealed that customer and legal expert support during the project could reduce the risk of misinterpreting the legislation. Verification and Validation of Legal Compliance are customer assignments. [Conclusions] Ambiguity resolution and legal compliance of requirements are based on the tacit knowledge of experienced team members or discussions between the team and the customer.